Mechanical strengths, drying shrinkage and pore structure of cement mortars with hydroxyethyl methyl cellulose - Wang, Shunxiang; Wang, Zhaojia; Huang, Tianyong; Wang, Peiming; Zhang, Guofang (Construction & building materials, 2022)
•Tensile bond strength keeps increasing with 0–3% HEMC.•Incorporating HEMC brings a significant increase in drying shrinkage.•Incorporating HEMC brings more macro and large capillary pores, and decreases interconnected pores.•Low flexural and compressive strengths may be attributed to more macro and large capillary pores. This paper aims at investigating the long-term mechanical strengths and drying shrinkage, as well as pore structure of cement mortars with hydroxyethyl methyl cellulose (HEMC). The results show that the 3-d flexural strength and compressive strength of cement mortars tend to decrease with the HEMC content increasing. At 28 d to 360 d, the strengths keep decreasing with the HEMC content increasing at 0–1%, and then increase from the minimum value with the HEMC content increasing at 1–3%, still being much lower than those of the control (0% HEMC). Throughout the curing age, both the tensile bond strength and the drying shrinkage value gradually increase with the HEMC content, to be nearly twice at 3% HEMC than those of the control. HEMC significantly delays the 3-d hydration of cement pastes, but has negligible retardation effect on the hydration after 28 d, to bring the similar late hydration degree of cement pastes with HEMC or not. With the HEMC content increasing in the range of 0–1%, incorporating HEMC brings the sharp increase of macro pores, large capillary pores and porosity, and decreases the interconnected pores to bring many more closed pores. Further increasing the HEMC content to 3%, macro pores and porosity decrease, large capillary pores slightly increase and interconnected pores have a negligible change. Obviously, the understanding on the performance development of cement mortars with HEMC is conducive to the better application of HEMC in dry-mix mortars to meet different requirements.